Development and application of DNA hydrogels in biosensing: current status and future implications - Chen, Zhuo; Mao, Kang; Xue, Jiaqi; Feng, Rida; Zhang, Kuankuan; Su, Junxia; Du, Wei; Ran, Jiabing; Yang, Changying; Yang, Zhugen; Zhang, Hua (Elsevier, 2025)
As emerging biopolymer materials, DNA hydrogels quickly respond to external stimuli to specifically recognize DNA through base pairing and have become widely used in the field of biosensors. Unlike traditional biosensing strategies, biosensors based on DNA hydrogels are highly specific, programmable and degradable. In this work, based on the advantages and wide application of DNA hydrogels in the field of biosensors, the progress of DNA hydrogel biosensors is systematically summarized in terms of the types of DNA hydrogels, detection principles and biosensor device integration. First, the types of DNA hydrogels used in biosensors are briefly introduced. Next, we thoroughly demonstrate the detection principles of DNA hydrogel biosensors; the detection principles depend on the recognition elements, signal elements, and transduction types of the DNA hydrogel used in the biosensor. In particular, we demonstrate the great potential of integrated devices and techniques used in DNA hydrogel biosensors, such as microfluidics and portable devices. Finally, the challenges and future development of DNA hydrogels in biosensing are discussed. This work can be used as a reference for research on biosensing analysis using DNA hydrogels.
Keywords: DNA hydrogel; Biosensor; Aptamer; Fluorescence; Colorimetry